2018
DOI: 10.1021/acscatal.8b02885
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Reducing (Diarylamino)anthracene Catalyst for Metal-Free Visible-Light Photocatalytic Fluoroalkylation

Abstract: Well-defined 9,10-bis­(di­(p-tert-butylphenyl)­amino)­anthracene serves as a photocatalyst for radical fluoroalkylation under visible light irradiation. The diarylamine (Donor)–anthracene (π conjugated system)–diarylamine (Donor) scaffolds are easily accessed by typical palladium-catalyzed cross-coupling protocols of the corresponding halogenated anthracenes with various lithium diarylamides. The anthracene-based photocatalyst exhibits high reducing power, leading to generation of versatile fluoroalkyl radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 124 publications
3
38
0
1
Order By: Relevance
“…In 1974, Dreeskamp, Koch and co-workers showed that the rate of ISC from the uorescent singlet to a triplet state can be increased in perylene by an intermolecular energy transfer to halogenated-naphthalene. 129,130,134 This precedence motivated us to take a closer look at our systems as the uorescence quantum yield of (DPA) 4 -Per is particularly low (4 ¼ 0.26) compared to perylene and triplet sensitizers are of great interest with many applications in phosphorescent materials, [135][136][137] phosphorescent bioimaging, 135,137,138 chemosensors, 135,137,139 photoinitiated polymerization, 137,140 photocatalysis, 137,[141][142][143][144] triplet-triplet annihilation based upconversion, 137,145,146 and oncological or antibacterial photodynamic therapy. 137,147,148 There are a few reports on triplet states of PDIs and these make use of bimolecular triplet sensitization, 149 incorporation of sulfur 150 or heavy metals such as Ir, 131,151,152 Pt, 153 Pd, 152,154 or Ru.…”
Section: Reactivity With Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1974, Dreeskamp, Koch and co-workers showed that the rate of ISC from the uorescent singlet to a triplet state can be increased in perylene by an intermolecular energy transfer to halogenated-naphthalene. 129,130,134 This precedence motivated us to take a closer look at our systems as the uorescence quantum yield of (DPA) 4 -Per is particularly low (4 ¼ 0.26) compared to perylene and triplet sensitizers are of great interest with many applications in phosphorescent materials, [135][136][137] phosphorescent bioimaging, 135,137,138 chemosensors, 135,137,139 photoinitiated polymerization, 137,140 photocatalysis, 137,[141][142][143][144] triplet-triplet annihilation based upconversion, 137,145,146 and oncological or antibacterial photodynamic therapy. 137,147,148 There are a few reports on triplet states of PDIs and these make use of bimolecular triplet sensitization, 149 incorporation of sulfur 150 or heavy metals such as Ir, 131,151,152 Pt, 153 Pd, 152,154 or Ru.…”
Section: Reactivity With Oxygenmentioning
confidence: 99%
“…This intriguing property is interesting for applications including molecular switches, 161,162 receptors, 162,163 photoactive dyads 164 or photocatalysis. 143,165 The donor-substituted counterpart, (DPA) 4 -Per, can be oxidized up to ve times according to cyclic voltammetry studies a Excited at the respective l abs (max) of S 1 ) S 0 . b Pre-exponential factors B n scaled to 100 and given in parentheses.…”
Section: Electrochemistrymentioning
confidence: 99%
“…In 2018, Eosin B‐catalyzed trifluoromethylation of coumarins 38 was reported by the Zhang and Deng group (Scheme a) . Koike and Akita group reported the keto‐trifluoromethylation of aromatic alkene 40 using 4 t Bu−BDA ((9,10‐bis( p ‐ t Bu−diphenylamino)anthracene)) (Scheme b) . In 2019, Zhang and Xu showed that 4CzIPN induces hydro‐trifluoromethylation of benzyl‐protected homoallylic alcohols and amines 42 concomitant with deprotection through HAT of the radical intermediate A (Scheme c) …”
Section: Strategies For Reductive Generation Of Fluoromethyl Radicalsmentioning
confidence: 99%
“…In 2018, the Koike and Akita group found that the above‐mentioned BDA can induce the oxy‐trifluoromethylation of alkenoic acid 44 with the sulfonium‐type reagent 1 f (Scheme a) . In addition, the authors developed a sulfonium‐based CF 2 H reagent 2 e for photocatalytic difluoromethylation in 2017 .…”
Section: Strategies For Reductive Generation Of Fluoromethyl Radicalsmentioning
confidence: 99%
See 1 more Smart Citation